1998
DOI: 10.1046/j.1365-2958.1998.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Shigella dysenteriae haem transport locus and its phylogenetic distribution in enteric bacteria

Abstract: SummaryThe ability to transport and use haemin as an iron source is frequently observed in clinical isolates of Shigella spp. and pathogenic Escherichia coli. We found that many of these haem-utilizing E. coli strains contain a gene that hybridizes at high stringency to the S. dysenteriae type 1 haem receptor gene, shuA. These shuA-positive strains belong to multiple phylogenetic groups and include clinical isolates from enteric, urinary tract and systemic infections. The distribution of shuA in these strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
134
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 56 publications
5
134
1
Order By: Relevance
“…This suggests that there is significant cross-talk among the V. cholerae permeases and that proteins of other transport systems can substitute for components of the haem transport system in part but not in its entirety. We have noted a similar phenomenon with the S. dysenteriae haem transport genes in which single mutations in genes other than the receptor have little effect, but loss of all the periplasmic and cytoplasmic transport protein genes eliminates transport in some strains (Wyckoff et al, 1998).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This suggests that there is significant cross-talk among the V. cholerae permeases and that proteins of other transport systems can substitute for components of the haem transport system in part but not in its entirety. We have noted a similar phenomenon with the S. dysenteriae haem transport genes in which single mutations in genes other than the receptor have little effect, but loss of all the periplasmic and cytoplasmic transport protein genes eliminates transport in some strains (Wyckoff et al, 1998).…”
Section: Discussionsupporting
confidence: 59%
“…Previous work had shown that there was no hybridization between a plasmid containing hutBCD and a cosmid clone containing hutA (unpublished observation), and physical mapping of the V. cholerae chromosome suggests that the hutA receptor gene is separated from the rest of the hut genes by more than a thousand kilobases (M. Trucksis, personal communication). The proteins encoded by the hut genes display significant homologies to proteins of the Y. enterocolitica (Hem) (Stojiljkovic and Hantke, 1994), Y. pestis (Hmu) (Hornung et al, 1996) and S. dysenteriae (Shu) (Wyckoff et al, 1998) haem transport loci. The hutBCD genes were required, in addition to hutA, to reconstitute the V. cholerae haem transport system in E. coli, indicating that they are haem transport genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Hmox1 may fulfill cytoprotective effects in Salmonella-infected phagocytes. Nevertheless, an induction of Hmox1 is also invariably associated with a reduction in the haem-associated iron pool [46], a mechanism which may contribute to the withholding of iron from internalized bacteria, some of which may be able to utilize haem molecules as an iron source via specific acquisition systems [47,48]. Given that the incorporation of freshly imported radioactive iron into ferritin multimers was markedly reduced upon addition of IFN-c (Fig.…”
mentioning
confidence: 99%
“…This cluster has a similar genetic organization and chromosome localization in many E. coli strains, suggesting that it was acquired by horizontal transfer (28).…”
mentioning
confidence: 93%
“…Such receptors are widespread among gram-negative species. The best-characterized receptors are Yersinia enterocolitica HemR (20) and Shigella dysenteriae ShuA (28). A more elaborate heme uptake system is present in fewer species, such as Serratia marcescens and Pseudomonas and Yersinia species.…”
mentioning
confidence: 99%